Revisión de la enseñanza de las ciencias en Gran Bretaña - West, R.W. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
After a brief review of the British educational system and the position of science education therein, the aims and methodology of the project known as «Secondary Science Curriculum Review» are introduced.